Pretreatment and Saccharification of Steam Exploded Waste of A Pharma Industry - MAMTA KUMARI; SUDHIR KUMAR; K. RAVIKANTH; RAJINDER SINGH CHAUHAN (International Journal of Pharma and Bio Sciences, 2010)
Herbal waste of processed medicinal plants of a local pharmaceutical industry was pretreated by steam explosion (1600C for 0.5 – 2.0 h), and the process was accelerated by the use of Conc. H2SO4 (0.5 – 2.0%, 1600C for 0.5 – 2.0 h), NaOH (0.5 – 2.0%, 1600C for 0.5 – 2.0 h). Significant increase in the content of reducing sugars was found after acid/alkali pretreatment of steam exploded herbal biomass. Maximum Reducing sugars obtained was 145.9 mg/g of herbal waste with 1.5% of H2SO4 at 1600C for 1.5 h. Bulk of herbal waste disposed off by pharma industry can act as secondary substrate as a source of fermentable sugars.